2021
DOI: 10.1177/10600280211023492
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pharmacist-Physician Collaborative Care on Therapeutic Inertia in Patients With Type 2 Diabetes

Abstract: Background Team-based care practice models have been shown to improve diabetes-related therapeutic inertia, yet the method and type of antidiabetic treatment intensification (TI) leading to improvements in glycemic control are not well understood. Objective To evaluate time to TI in a pharmacist-physician practice model (PPM) as compared with usual medical care (UMC), explore the method and type of antidiabetic TI, and evaluate achievement of hemoglobin A1C (A1C) goal among each cohort. Methods This was a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Other studies that looked at the implementation of pharmacist-involved collaborative care in a primary healthcare setting improved several diabetes-related outcomes over 17 months [HbA 1c (7.5% vs. 6.8%), low-density lipoprotein cholesterol (3.7 mmol/L vs. 2.8 mmol/L), total cholesterol (5.43 mmol/L vs. 4.34 mmol/L), and body mass index (30.42 kg/m 2 vs. 30.17 kg/m 2 )] [ 16 ], achieved a longer time in target range for systolic blood pressure compared with control (usual care) [ 17 ] and a shorter time to therapeutic intensification and improvement in A1C goal achievement was observed with pharmacist-physician care compared with usual medical care [ 18 ]. These findings suggest that pharmacist-physician collaborative care may be one of several interventions necessary to improve the diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that looked at the implementation of pharmacist-involved collaborative care in a primary healthcare setting improved several diabetes-related outcomes over 17 months [HbA 1c (7.5% vs. 6.8%), low-density lipoprotein cholesterol (3.7 mmol/L vs. 2.8 mmol/L), total cholesterol (5.43 mmol/L vs. 4.34 mmol/L), and body mass index (30.42 kg/m 2 vs. 30.17 kg/m 2 )] [ 16 ], achieved a longer time in target range for systolic blood pressure compared with control (usual care) [ 17 ] and a shorter time to therapeutic intensification and improvement in A1C goal achievement was observed with pharmacist-physician care compared with usual medical care [ 18 ]. These findings suggest that pharmacist-physician collaborative care may be one of several interventions necessary to improve the diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…The co-visit model not only reduces the burden placed on PCPs to manage chronic disease states and expands patient access, but also results in improved health outcomes, such as improvement in hemoglobin A1c in patients with type 2 DM 3,4 . Previous studies have found that the co-visit model generated 4924.41 dollars in additional income over 14 half-days, allowed providers to see, on average, 1.3 additional patients per half day compared to individual visits, and justified the addition of one full-time equivalent pharmacist position 1,2,9 .…”
Section: Introductionmentioning
confidence: 99%